Forensic epidemiology in the global context - Loue, Sana (Springer New York, 2013)
As globalization causes profound changes in business, industry, and trade,it can also have significant effects on populations, environments, and individuals.These effects may be harmful, resulting in injury or illness, prompting the critical question: How best to correct wrongs caused to individuals, communities, and/or the environment of onecountry by the actions of individuals or corporations of another?  Possible answers lie in an emerging discipline. Forensic Epidemiology in the Global Context opens meaningful windows onto the processes of forensic epidemiology, the roles of the epidemiologist in civil disputes, and the potential contribution of the field to legal and justice efforts worldwide. Case examples from the U.K., Nigeria, Ecuador, Romania, and Australia illustrate commonly used methodologies and the challenges involved in their use in U.S. and international courts of law. A chapter on expert testimony takes readers through qualification and admissibility issues, report requirements, and working with attorneys. Included in the coverage: Forensic epidemiology in the international legal arena. The epidemiologist as an expert in litigation. Epidemiological evidence in tort law: dispatches from the U.K. Liability for occupational exposure: the role of epidemiology. Forensic epidemiology and environmental justice. Forensic epidemiology, pathology, ethnics, and human rights. By emphasizing both the scientific and legal components of the equation, Forensic Epidemiology in the Global Context gives researchers and graduate students in epidemiology a unique and timely guide to the present and future of an increasingly salient field.